Depressive symptoms in primary care pregnant women: prevalence and associated factors - Dell'Osbel, Rafaela Santi; Gregoletto, Maria Luisa Oliveira; Cremonese, Cleber (ABCS Health Sciences, 2019)
Introduction: The onset of emotional disorders early in pregnancy is frequent, including depressive symptoms (DS) such as guilt, lack of appetite and energy. Objective: To measure the prevalence of depressive symptoms and associated factors in pregnant women attending primary care. Methods: Cross-sectional observational epidemiological study of pregnant women, who attend primary care in Caxias do Sul, Rio Grande do Sul, Brazil. Depressive symptoms were assessed using Patient Health Questionnaire (PHQ-9). Gross analysis was performed, in which prevalence ratios (PR) and respective confidence intervals (CI 95%) were calculated. The comparison of categorical variables occurred through the Chi-square test. The adjusted analysis was performed by Poisson regression, using the backwards technique, where the final model was constructed from the variables with p≤0.20 in the gross analysis. Results: The sample consisted of 76 pregnant women, of these 46.1% had depressive symptoms. The average age was 26.6 years (±5.95) and 72.4% were married or in a stable union. There was a significant association between depressive symptoms and marital status (PR: 1.54; 95% CI 1.00-2.37; p=0.045) and the occurrence of abortion in other pregnancies (PR: 1.72; 95% CI 1, 08-2.74; p=0.022). Conclusion: There was a high prevalence of depressive symptoms compared to regional studies in the pregnant women investigated. Factors associated with the outcome were marital status and history of abortion, which may cause problems during pregnancy and postpartum. Thus, there is a need for tools and strategies to identify the presence of depressive symptoms in early pregnancy, so that they can be diagnosed and treated.